Corporate governance and financial constraints in family controlled firms: Evidence from Malaysia - Chu, Ei Yet; Lai, Tian So; Song, Saw Imm (Universiti Malaysia Sarawak, 2016)
The hypothesis of financial constraints suggests that firms will be denied profitable investment due to inaccessible to external capital markets as debt and equity financing are no longer perfect substitutions after firms utilize internal capital. In view of reduced investments during global financial crisis in 2008-2009, the study investigates 157 firms, whether they face the issues of financial constraints in Malaysia. In general, non-family firms rely heavily on the external debt market while family controlled firms utilizing internal cash and reducing their dependence on debt market for their investments, confirming financial constraints in family firms. However, the presence of CEO duality does not exaggerate the problem of financial constraints, but rather leads family firms to become stagnant in their investments. Independent directors appear to be ineffective in governing family firms in issuing finances for investment. Apparently, their presence in family firms reduces firms’ investment opportunities either through internal cash and external debt financing, which could reduce shareholders’ value in the long-term.